Attitudes of medical students to general practice: a multinational cross-sectional survey - Avian, Alexander; Poggenburg, Stephanie; Schaffler-Schaden, Dagmar; Hoffmann, Kathryn; Sanftenberg, Linda; Loukanova, Svetla; Bachler, Herbert; Gehrke-Beck, Sabine; Ster, Marija Petek; Becker, Annette; Herrmann, Markus; Frese, Thomas; et al. (Family practice, 2021)
General practitioners; medical school; motivation; primary health care; questionnaire design; students